An eLearning module for the biomechanical analysis of motor performance in sports - a learning tool for academic teaching - Kibele, A. (International Journal of Computer Science in Sport, 2011)
A teaching approach is introduced to supplement regular classroom teaching in elementary physics through an eLearning module. The approach aims to promote a multimodal learning in the field of sports biomechanics based on the benefits of a multimedial learning environment. This paper outlines the basic structure and a first step towards an evaluation of the given eLearning units when being used as an add-on to a university seminar on Biomechanics in Sports. The results of the evaluation indicate that eLearning material should be used in self-directed learning settings only with learners having a precise guideline on exactly what to do and how long to do it.